S100A8 alarmin supports IL-6 and metalloproteinase-9 production by fibroblasts in the synovial microenvironment of peripheral spondyloarthritis - Arias, José L.; Funes, Samanta C.; Blas, Rodrigo; Callegari, Eduardo; Eliçabe, Ricardo J.; Páez, María D.; Munarriz, Alicia; Pardo-Hidalgo, Rodolfo; Tamashiro, Héctor; Di Genaro, María S. (Frontiers in Immunology, 2023)
Spondyloarthritis (SpA) is a common autoinflammatory disease. S100A8/S100A9 alarmin is strongly expressed in the synovial sublining layers of psoriatic arthritis. S100A8/S100A9 is the most abundant protein in rheumatoid arthritis synovial fluid (SF) and has a key role in promoting IL-6 expression in fibroblast-like synoviocytes (FLS). The molecular mechanisms and the role of S100-alarmins in the synovial microenvironment of SpA have never been demonstrated. Here, we confirm the effect of the synovial microenvironment of peripheral SpA on interleukin-6 (IL-6) and metalloproteinase (MMP)-9 production by FLS. MMP-9 expression and activity were detected, which were reduced in the presence of anti-IL-6R. Analyzing cell signaling mechanisms, we found that stimulation with IL-6 co-triggered MMP-9 and IL-10 secretion. MMP-9 secretion depended on JNK and p38 MAPKs, whereas IL-10 secretion was dependent on the JAK pathway as a potential feedback mechanism controlling IL-6-induced MMP-9 expression. Using a proteomic approach, we identified S100A8 in the peripheral SpA SF. This presence was confirmed by immunoblotting. S100A8 increased the IL-6 secretion via ERK and p38 MAPK pathways. Furthermore, anti-S100A8/A9 reduced both IL-6 and MMP-9 production induced by SpA SF in FLS. Our data reveal a marked relationship between S100A8 alarmin with IL-6 and MMP-9 secretion by FLS in the real synovial microenvironment of peripheral SpA. These results identify a mechanism linking S100A8 to the pathogenesis of peripheral SpA.